Tanggung Gugat PT CIMB Niaga Auto Finance atas Perbuatan Melawan Hukum Pekerja - Prastya, Handyka Ilham; Lyanthi, Merline Eva (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This thesis analyzes the corporate legal liability or liability of PT CIMB Niaga Auto Finance (CNAF) for alleged Unlawful Acts (PMH) against its workers. This research is driven by the legal complications surrounding the problematic of Termination of Employment Relationships carried out by one party that is not procedural, which is specifically reflected in the Industrial Relations Court Decision at the Surabaya District Court Number 105/Pdt.Sus-PHI/2024/PN Sby. The purpose of this research is to analyze and understand the form of liability that must be borne by the company, as well as to assess the reasons for the judge's legal considerations in Decision No. 105/Pdt.Sus-PHI/2024/PN Sby. This study employs a normative legal research methodology linked to applicable legal regulations. The approaches used include the Statutory Approach, Conceptual Approach and Case Approach by analyzing Decision Number 105/Pdt.Sus-PHI/2024/PN Sby. The analysis results show that the unilateral termination of employment without valid proof of the alleged violation of the code of ethics by workers has fulfilled the components of Unlawful Acts (PMH) such as Article 1365 of the Civil Code. Thus, PT CIMB Niaga Auto Finance has liability for worker losses, both based on corporate liability and vicarious liability (employer's liability for the actions of subordinates) according to Article 1367 of the Civil Code. The judge's reason in the decision is considered to have applied the principle of progressive law, by affirming the company's liability and providing compensation, as an effort to realize substantive justice and protection for workers as a vulnerable party in industrial relations.